A Bibliometric Analysis of the Use of Augmented Reality in Ethnomathematics Education - Ratu Mauladaniyati; Sumarni Sumarni (Universitas Negeri Surabaya, 2025)
One area that has been gaining increasing attention is the integration of Augmented Reality (AR) technologies in mathematics education, especially within the context of ethnomathematics. This study aims to explore trends, developments, and directions of research related to the use of Augmented Reality (AR) technology in ethnomathematics education through a bibliometric approach. By utilizing the Scopus database, relevant scientific articles were selected based on keywords such as